2023
DOI: 10.1536/ihj.22-498
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Outcomes of Elective Paclitaxel-Coated Balloon Angioplasty in Comparison with Drug-Eluting Stents for De Novo Coronary Lesions in Large Vessels

Abstract: We retrospectively examined the feasibility of paclitaxel-coated balloon (PCB) angioplasty for de novo stenosis in large coronary vessels (LV; pre-or postprocedural reference vessel diameter !2.75 mm) in comparison with placement of drug-eluting stents (DESs).Consecutive de novo stenotic lesions in the LV electively and successfully treated with either PCB (n = 73) or DESs (n = 81) from January 2016 to December 2018 at our center were included. The primary endpoint was the incidence of target lesion failure (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Second, PCB angioplasty showed good angiographic outcomes at chronic phase represented in small LLL ( Table 4 ). The small (less than 0.10 mm) mean magnitudes of LLL after PCB angioplasty were consistent in the cases of CCS by the elective procedures regardless of vessel sizes [ 1 , 19 , 20 , 21 , 22 ]. A small LLL gave low incidences of TLR including TVR; those in turn, contributed to the low and statistically equivalent frequencies of composite MACE compared to DES ( Figure 2 , Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Second, PCB angioplasty showed good angiographic outcomes at chronic phase represented in small LLL ( Table 4 ). The small (less than 0.10 mm) mean magnitudes of LLL after PCB angioplasty were consistent in the cases of CCS by the elective procedures regardless of vessel sizes [ 1 , 19 , 20 , 21 , 22 ]. A small LLL gave low incidences of TLR including TVR; those in turn, contributed to the low and statistically equivalent frequencies of composite MACE compared to DES ( Figure 2 , Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 56%
“…This unique angiographic phenomenon at chronic phase after PCB angioplasty, LLE, was also observed in cases of ACS [ 13 , 15 , 24 , 25 , 26 ] ( Table 4 ). Similarly, LLE was observed in approximately half of the angiographic followed-up lesions after PCB angioplasty for ACS ( Table 4 ) as with after for CCS [ 20 , 21 , 22 , 23 ]. Greater lumen enlargement in ACS compared to CCS with the significant increase in the vessel and lumen area, and significant decrease in the plaque area [ 24 ] was reported.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Twelve studies reported clinical follow-up data on CVD, MI and TLR. [13][14][15][16][17][18][19][20][21][22][23][24] No differences were found between DCB and DES for the risk of CVD [1.1% vs 3.2%; RR: 0.49 (95% CI: 0.23 -1.03; p=0.06; I 2 =0%] (Figure 2); MI [0.3% vs 1.5%; RR: 0.48 (95% CI: 0.16 -1.45; p=0.89; I 2 =0%] (Figure 3), and TLR [3.7% vs 6.1%; RR: 0.73 (95% CI: 0.40 -1.34; p=0.32; I 2 =27%] (Figure 4).…”
Section: Endpointsmentioning
confidence: 99%
“…Eight studies reported data on ACD 14,[16][17][18][19][20]24,25 . At follow-up, no differences were found between DCB and DES for the risk of ACD [5.5% vs 7.8%; RR: 0.78 (95% CI: 0.57 -1.07; p=0.12; I 2 =0%] (Figure 5).…”
Section: Endpointsmentioning
confidence: 99%